Operation Breadbasket : An Untold Story of Civil Rights in Chicago, 1966-1971 - Deppe, Martin L. (Book collections on Project MUSE., 2017)
"Operation Breadbasket is a narrative of the Southern Christian Leadership Conference's Operation Breadbasket, 1966-1971, an economic empowerment project that Martin Luther King Jr brought to Chicago as part of the Chicago Freedom Movement. Rev. Martin L. Deppe was a founding and active member of Breadbasket's steering committee throughout the life of this program. Using the power of the pulpit to galvanize consumer support including occasional economic withdrawal ("Don't Buy") efforts, the participating ministers, the project negotiated for a fair share of jobs in the African American community of Chicago, and in time added products and services originating from that community. By the end of six years, Breadbasket's fifteen "covenants" with milk, soft drink, chain store and other consumer-oriented industries, brought approximately $57 million dollars of new income into the black community annually. The program ended when the project's national director, Rev. Jesse Jackson, resigned in December 1971, and essentially took the program out of SCLC into his own Operation PUSH, later Rainbow PUSH. This book is both a history of Operation Breadbasket, and a memoir of life in it as written by one of Breadbasket's most active participants. Deppe uses his extensive files--steering committee minutes, memoranda, brochures, letters, sermonic material, Chicago Defender archives, colleagues' files--along with extensive new research, including interviews with several surviving participants."--Provided by publisher.